2017
DOI: 10.1371/journal.pone.0181830
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoperone rescue of vasopressin 2 receptor mutants reveals unexpected constitutive activity and coupling bias

Abstract: Pharmacoperones are small molecules that diffuse into cells and rescue misfolded, mistrafficked protein mutants, restoring their function. These substances act with high target specificity, serving as templates to fold (or refold) receptors, enzymes, ion channels or other proteins and enable them to pass the scrutiny of the cellular quality control system (“rescue”). In the present study we demonstrate that a rescued mutant (L83Q) of the vasopressin type 2 receptor (V2R), shows a strong bias for Gs coupling un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Since they are trapped in the ER, their presence on the plasma membrane are reduced and consequently their agonist sensitivity were reduced. Some of the intracellularly trapped mutants can be rescued using with PCs and it is shown that AVPR2 mutants could be rescued by this strategy [14,[20][21][22]. With the help of PCs, which are cell-permeable small molecules, mutant receptors can fold properly and pass the ER quality control system.…”
Section: Discussionmentioning
confidence: 99%
“…Since they are trapped in the ER, their presence on the plasma membrane are reduced and consequently their agonist sensitivity were reduced. Some of the intracellularly trapped mutants can be rescued using with PCs and it is shown that AVPR2 mutants could be rescued by this strategy [14,[20][21][22]. With the help of PCs, which are cell-permeable small molecules, mutant receptors can fold properly and pass the ER quality control system.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, these methods mainly involve the following mechanisms: (1) AVPR2 antagonists and cell-permeable AVPR2 antagonists act as molecular chaperones and are mainly administered to patients with AVPR2 missense mutations[ 19 ]. Targeting chemical and molecular chaperones appropriately corrects the point mutations that cause misfolded disease-causing proteins, rescuing mutant proteins from ER retention and allowing correctly folded proteins to be delivered in cells[ 19 , 20 ]; (2) AVPR2 agonists, some of which are cell permeability agonists, can bind AVPR2 mutants trapped in the ER, but they do not stabilize their conformation and can directly activate AVPR2 mutants within these cells by signaling to transmit a preformed receptor-G protein-adenylate cyclase complex. The subsequent generation of cAMP activates PKA, resulting in AQP2 phosphorylation and plasma membrane expression, thereby attenuating the NDI phenotype[ 4 , 19 ]; (3) Some classic treatment modalities, including vasopressin analogs, prostaglandin receptor agonists, hormone receptor agonists, and cGMP phosphodiesterase inhibitors, can bypass the defective AVPR2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, biased responses can be elicited by biased ligands, biased receptors, or system bias, all of which can lead to preferential signaling through G proteins or β-arrestins ( Smith et al, 2018 ). Biased agonism has been studied at several GPCRs, including G q/11 -coupled receptors ( Sanchez-Fernandez et al, 2013 ; Cabana et al, 2015 ; Mancini et al, 2015 ; Janovick et al, 2017 ; Teixeira et al, 2017 ). However, TRH-R has not received much attention in this regard.…”
Section: Thyrotropin-releasing Hormone Receptor-mediated Signalingmentioning
confidence: 99%